Dewan Komisaris, Kepemilikan Manajerial, dan Leverage: Determinan Kinerja Keuangan Perusahaan - Dyah Ayu Retno Inten (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to make a new contribution by examining in greater detail the effects of the Board of Commissioners, managerial ownership, and leverage on financial performance in technology companies. The research design employed in this study is quantitative. The population used in this study consists of 47 technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2025; this study utilizes secondary data. The analytical method employed is multiple linear regression. The data analysis techniques include classical assumption tests and hypothesis testing conducted using multiple regression. This study will be analyzed using Statistical Package for Social Sciences version 27. The findings indicate that the Board of Commissioners has a positive effect on financial performance, whereas managerial ownership and leverage do not affect financial performance. The implications of this study are expected to improve the financial performance of the technology sector by focusing on the composition and number of audit committee members tailored to the company’s needs.